Perception of Pain during Rapid Palatal Expansion - Gökhan Önçağ; Furkan Dindaroğlu; Servet Doğan (Galenos Yayinevi, 2011)
Aim:The aim of this study is to study the differences in the perception of pain in different parts of the face during rapid palatal expansion (RPE). The change in intensity of pain with time is examined. We also examined differences in pain perception between males and females.Subjects and Methods:The study sample consisted of 30 patients (16 males, 14 females) between the ages of 13 and 15 years (mean 14.4 years). Hyrax expander was activated two times a day during a period of 10 days (0.5 mm /day). A color pain scale was used to assess the level of pain during RPE. Mann-Whitney U test and Friedman Test were conducted for statistical analysis.Results:Statistically significant differences were found in average pain scores attributed to different regions (p<0.001). The decrease in the overall pain perception in all 8 different regions occurred during 10 days was statistically significant (p<0.001). There were no significant differences in pain perception between males and females (p>0.05).Conclusion:There were no significant differences in pain perception between males and females. Pain is found to be most severe in the dental arc region, while it decreases with the distance from the activation region. Pain shows a decrease following the first activation.